The flea beetle fauna of Mêdog, China, with description of three new species (Coleoptera: Chrysomelidae: Galerucinae: Alticitae) - Peng, Ying-Ying; Liang, Zu-Long; Ruan, Yong-Ying (Zootaxa, 2026)
Based on the study of specimens from China’s two largest flea beetle collections (SZPU and IZCAS), this paper reviews the flea beetle fauna (Alticitae) of Mêdog, Xizang, China. In addition to a catalogue and photographs for most species, three new species from Mêdog are described: Sinocrepis medogensis sp. nov., Longitarsus acutus sp. nov., and Longitarsus gracilicallus sp. nov. Keys to Sinocrepis species of China and to Longitarsus species of Mêdog are provided. Moreover, Longitarsus yangsoensis Chen, 1939 syn. nov. is proposed as a junior synonym of Longitarsus championi Maulik, 1926; and Longitarsus ochraceicornis Maulik, 1926 is recorded from China for the first time.